2018
DOI: 10.1200/jgo.2016.008276
|View full text |Cite
|
Sign up to set email alerts
|

Video-Teleconferencing in Pediatric Neuro-Oncology: Ten Years of Experience

Abstract: PurposeThe management of central nervous system tumors is challenging in low- and middle-income countries. Little is known about applicability of twinning initiatives with high-income countries in neuro-oncology. In 2004, a monthly neuro-oncology video-teleconference program was started between King Hussein Cancer Center (Amman, Jordan) and the Hospital for Sick Children (Toronto, Ontario, Canada). More than 100 conferences were held and > 400 cases were discussed. The aim of this work was to assess the sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
(18 reference statements)
0
30
0
Order By: Relevance
“…Ongoing efforts by the global academic and medical communities to advocate for national pediatric cancer registries and pediatric cancer national healthcare plans, and to improve available infrastructure and care delivery through twinning models, planning of healthcare delivery networks, and cooperative national and regional groups, are all mechanisms by which patient outcome may be improved for children with RMS and other childhood cancers requiring complex multidisciplinary care. The successes reported in several centers in UMIC and LMIC, especially with involvement of NGOs for proper resource allocation and infrastructure development, serve as a model for refinement of pediatric cancer care in areas with limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing efforts by the global academic and medical communities to advocate for national pediatric cancer registries and pediatric cancer national healthcare plans, and to improve available infrastructure and care delivery through twinning models, planning of healthcare delivery networks, and cooperative national and regional groups, are all mechanisms by which patient outcome may be improved for children with RMS and other childhood cancers requiring complex multidisciplinary care. The successes reported in several centers in UMIC and LMIC, especially with involvement of NGOs for proper resource allocation and infrastructure development, serve as a model for refinement of pediatric cancer care in areas with limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…On average 4 to 5 patients were discussed during each 1-hour session. The benefits of this interaction quickly became evident for all participants (92)(93)(94)(95)(96). The group conducted a series of research projects together, and found that 17 of 44 (39%) children with high-grade malignant brain tumour cases at KHCC over 10 years had defective mismatch repair (MMR) genes, compared to less than 4% in North America (97,98).…”
Section: Strategic Aims Include Ensuring That Drug Development For Chmentioning
confidence: 99%
“…Expanding the telemedicine-based collaboration between global highly specialized centers and the Chilean hospitals may represent a promising avenue to facilitate long-distance consultation, provide continuous educational opportunities, and improve management plans. 22 - 24 …”
Section: Discussionmentioning
confidence: 99%